The Neverending 90s in Serbia - Nađa Bobičić; Vanja Petrović (Politikon)
Right-wing actors—conservative politicians, public intellectuals, and the Serbian Orthodox Church—have been influential in contemporary Serbia since the early 1990s, playing a formative role in its anti-gender movement. This study advances our understanding of how anti-gender mobilization draws from its local context. Drawing on Judith Butler’s concept of gender phantasm and Andrea Pető’s concept of gender as symbolic glue, this analysis examines two documents: the 1992 “Warning” resolution and Patriarch Pavle’s 1995 Christmas message. These texts enable mapping of actors and succinctly encapsulate the ideological imaginaries of the conservative elite who remain active. The ideological imaginary uniquely draws from rhetoric used to justify regional wars, serving as the phantasmic foundation of contemporary anti-gender mobilizations. Since right-wing actors operated within a contested space, the study acknowledges the unwavering feminist and pacifist left-wing opposition.